Dança criativa e o desenvolvimento do potencial criativo dos alunos do fundamental I - Costa, Luana Nascimento da (2021)
The research aimed to investigate the practices of creative dance, and its influences in the development of the child´s creative potential, according to Rudolf Laban studies of moviment from its main strands, emphasizing the characteristics of: space, weight and time. Providing the understanding of the possibilities that creative dance covers, and the benefits it brings to the student´s life. Through this proposal was carried out a field survey at the School Municipal Professor João Chrysóstomo de Oliveira with children between 8 and 12 years old, stimulating the teaching of dance, as a physical potentiator, mental and emotional. This research adressed the study of creative dance and the experiences of motor coordination, new forms of body movement and expressiveness, using the contents that the research explained, through the methodological proposal, in order to develop the possibilities,of creation, sensitivity, increasing the sense-perceptive vocabulary. The instruments used were playful activities, exercises that work spontaneity, the creation and activities in groups. To conclude the results, through pratical classes and interviews with students, it can be noted that creative dance enhances it creative abilities, So the application of creative activies with children is paramount for the development of their skills in all areas, providing a creative, sensitive and empowering environment for lasting learning.